2001
DOI: 10.1038/modpathol.3880337
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Pathology of Inhalational Anthrax I: Quantitative Microscopic Findings

Abstract: Forty-one cases of documented inhalational anthrax from the Sverdlovsk epidemic of 1979 traced to release of aerosols of Bacillus anthracis at a secret biologic-agent production facility were evaluated by semiquantitative histopathologic analysis of tissue concentrations of organisms, inflammation, hemorrhage, and other lesions in the mediastinum, mediastinal lymph nodes, bronchi, lungs, heart, spleen, liver, intestines, kidneys, adrenal glands, and central nervous system. These data were correlated with clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
200
5
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(220 citation statements)
references
References 19 publications
14
200
5
1
Order By: Relevance
“…We evaluated protection following ANTXR silencing in the AD293 human embryonic kidney cell line. The kidneys are targets of anthrax pathogenesis during human inhalational anthrax; capillaritis, intratubular bleeding, and tubular necrosis are observed by histopathology (21). Hemorrhaging in the kidney is also observed in animal models of gastrointestinal anthrax (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated protection following ANTXR silencing in the AD293 human embryonic kidney cell line. The kidneys are targets of anthrax pathogenesis during human inhalational anthrax; capillaritis, intratubular bleeding, and tubular necrosis are observed by histopathology (21). Hemorrhaging in the kidney is also observed in animal models of gastrointestinal anthrax (25).…”
Section: Discussionmentioning
confidence: 99%
“…The kidneys are among the organs that are harmed in human cases of inhalational anthrax, with evidence of intratubular bleeding and tubular necrosis found by histopathology (21). Based on a previous study, we knew that human embryonic kidney 293 (HEK293) cells were susceptible to cleavage of MEK1 by LeTx and, thus, deduced that these cells had to express at least one of two ANTXRs.…”
Section: Anthrax Toxin Receptor Transcript and Protein Expressions Inmentioning
confidence: 99%
“…In addition, we showed that LT enhances vascular cell adhesion molecule-1 (VCAM-1) expression and monocyte adhesion on the surface of tumor necrosis factor-␣ (TNF)-activated primary human endothelial cells, suggesting a possible link between LT and the vasculitis associated with anthrax (9,22,23). The enhanced expression of VCAM-1 was found to be transcriptionally driven by the cooperative activation of the VCAM1-regulating transcription factors, interferon regulatory factor-1 (IRF-1), and NF-B (24).…”
mentioning
confidence: 98%
“…The high mortality resulting from systemic anthrax infection is generally associated with profound vascular pathologies, including vascular leakage, edema, hemorrhage, vasculitis, and a poor immune response (7)(8)(9). Importantly, many of these symptoms are also observed in animals treated with purified LT (10 -14).…”
mentioning
confidence: 99%
“…18 Various types of liver damage induced hemostatic abnormalities and hemorrhage. 19 Previous studies have revealed that anthrax induces liver damage; invasions of bacterium B. anthracis have been observed frequently in the liver of infected patients [20][21][22] and animals. 15,23,24 These results prompted us to investigate whether coagulant factor defects are associated with LT-induced liver damage.…”
Section: Introductionmentioning
confidence: 99%